Effects of Classroom Acoustics and Self-Reported Noise Exposure on Teachers' Well-Being. (February 2013) - Kristiansen, Jesper; Persson, Roger; Lund, Søren Peter; Shibuya, Hitomi; Nielsen, Per Møberg
Beyond noise annoyance and voice problems, little is known about the effects that noise and poor classroom acoustics have on teachers' health and well-being. The aim of this field study was therefore to investigate the effects of perceived noise exposure and classroom reverberation on measures of well-being. Data on self-reported noise exposure, job satisfaction, fatigue after work, and interest in leaving the job were obtained from 283 teachers at 10 schools in Copenhagen, Denmark. In addition, the schools' acoustical working environment was classified as "low reverberation time (RT)" (3 schools, RT = 0.41-0.47 s), "medium RT" (3 schools, RT = 0.50-0.53 s), or "high RT" (4 schools, RT = 0.59-0.73 s). Significant associations were found between high RT and noise exposure, and, respectively, low job satisfaction, lack of energy after work, and interest in leaving the job. Noise exposure was also associated with lack of motivation and sleepiness. The results demonstrate the importance of good classroom acoustic conditions for teachers' well-being.